2017
DOI: 10.14719/pst.2017.4.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promoting Rhizobacteria (PGPR) and Plutella xylostella (L.) (Lepidoptera: Plutellidae) interaction as a resistance inductor factor in Brassica oleracea var. capitata

Abstract: Resistance of Plutella xylostella populations to chemical insecticides has made its management difficult, and the utilization of resistant cabbage cultivars has been shown to be a useful alternative. The objective of this study was to demonstrate the induction of cabbage plant resistance to P. xylostella using PGPR and injuries caused by the pest larvae as elicitors. Therefore, we evaluated the insects' responses utilizing a specific bioassay. Furthermore, this assay was used for selecting a PGPR strain that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The influence of this rhizobacterium (EN4) on post-embryonic viability suggests that there is a cumulative effect of reductions in larval and pupal viability, resulting in a greater increase in total mortality. Similar results were observed by Crialesi et al (2017), who showed that EN4 generally caused low larval and pupal viability, as well as reduction in pupal duration.…”
Section: Larval Pupal Viability and Pupal Durationsupporting
confidence: 87%
“…The influence of this rhizobacterium (EN4) on post-embryonic viability suggests that there is a cumulative effect of reductions in larval and pupal viability, resulting in a greater increase in total mortality. Similar results were observed by Crialesi et al (2017), who showed that EN4 generally caused low larval and pupal viability, as well as reduction in pupal duration.…”
Section: Larval Pupal Viability and Pupal Durationsupporting
confidence: 87%
“…Several studies have examined the seed bio-priming method to enhance yield or biomass production (Raj et al, 2004;Abuamsha et al, 2011b;Manrique et al, 2019), yet few studies have included plant resistance to insect herbivores (Crialesi et al, 2017;Thuler et al, 2017). Therefore, we investigated cabbage bacterization effects on plant biomass and resistance to three common insect herbivores of cabbage plants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a few other bacteria-plant-insect systems show a systemic negative effect from rhizobacterial inoculation on leaf area consumed by insects (Zehnder et al, 1997;Commare et al, 2002;Saravanakumar et al, 2008). For example, leaf area consumed by P. xylostella was negatively affected, after B. oleracea seed inoculation with endophytic Kluyvera ascorbata EN4, when the insects fed on detached leaves (Crialesi et al, 2017). On the other hand, neutral effects from microbes have previously also been recorded, where consumed leaf area by Spodoptera littoralis was not affected by presence of soil microbes in the soil of maize plants (D'Alessandro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%